Health promotion activity in Kampung Rosob, Pitas - Yusof Ibrahim; Myo Thura Zaw; Mohd Johari Mohd Shafuwan; Navien Supramaniam; Ahmad Izzuddin Anuar; Ivorenne Yvonne Joannes Akim; Justina Joseph; Khoo, Chin Wei; Law, Yee Ching; Leong, Sin Chi; Thirashini Chanla Chandran; Mahanim Sundang; et al. (Universiti Malaysia Sabah, 2015)
We, group 3 members which consist of 9 medical students, 8 who recently finished 1st year Medical program and 1 who recently finished 2nd year Medical program and 5 nursing students went to Kg Rosob, Pitas for health promotion from 24th August 2015 to 2nd September 2015. During our visit in the village, we started with opening ceremony once we reached the village as we have already planned with the head of the village to do opening ceremony before any activities in the village. The next day, we started our rapid rural appraisal (RRA) to get overview of the village and health problems and then we planned activities according to information from RRA to promote the health of villagers by various actions such as 1. RRA which indudes direct or field observation, secondary data resources, key informant Interview, individual interview, group meeting or interview and discussion, house-house visit, and social mapping. 2. Health education by means of talk such as breast and cervix cancer , demonstration , exhibitions , and health screening . 3. Life style and behavioral changes; for example: talk for high blood pressure , personal hygiene practice, school activities ,mini sports day and aerobic exercise. 4. Nutritional education; for example: talk on balanced diet, proper way to take medicine and good eating habits. 5. Education ; fun learning for year 5 students as a preparation for them to sit for next year UPSR examination. And involved in motivation camp for year 6 students as a preparation for their UPSR examination in August. 6.Voluntary works ; such as gotong royong to clean the compound of the village for the benefits of their health, and also killing the hair louse for the infected girls in the dorm.